Constructing a Destination Gestalt Model: Brand Gestalt, Brand Attitude, and Revisit Intention - Walean, Ronny H. (Animo Repository, 2023)
This study proposes and tests a structural model that integrates brand gestalt, brand attitude, and revisit intention in the context of tourism destinations. Specifically, the study investigated the influences of 4S brand gestalt dimensions (i.e., story, sensescape, servicescape, and stakeholder) on tourists’ attitudes and intention to revisit a destination. Survey-based data were collected from visitors of North Sulawesi, Indonesia (n = 357). Findings from the structural equations modeling analysis indicate that the two underlying dimensions of brand gestalt (i.e., story and sensescape) significantly influence brand attitude and revisit intention. Additionally, the brand attitude has a significant effect on revisit intention. Finally, while the brand story is the most salient predictor of brand attitude, sensescape has a greater impact on revisit intention. The theoretical and managerial implications of these findings are proposed.